2016
DOI: 10.1051/0004-6361/201628509
|View full text |Cite
|
Sign up to set email alerts
|

Setting the volatile composition of (exo)planet-building material

Abstract: Context. The atmospheres of extrasolar planets are thought to be built largely through accretion of pebbles and planetesimals. Such pebbles are also the building blocks of comets. The chemical composition of their volatiles are usually taken to be inherited from the ices in the collapsing cloud. However, chemistry in the protoplanetary disk midplane can modify the composition of ices and gases. Aims. To investigate if and how chemical evolution affects the abundances and distributions of key volatile species i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
340
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(355 citation statements)
references
References 80 publications
13
340
2
Order By: Relevance
“…A similar distribution of gas-phase H 2 O in the midplane of a Herbig Ae disk is reported in Figure 1 of Woitke et al (2009b). Here we also note that Eistrup et al (2016) calculated the chemical evolution of a disk midplane under both molecular and atomic initial conditions as initial chemical abundances. They showed that in the latter atomic conditions, the abundance of H 2 O gas and ice around the H 2 O snowline (∼ 10 −6 ) is smaller than that for molecular initial abundances (∼ 10 −4 ).…”
Section: The Distributions Of H 2 O Gas and Icesupporting
confidence: 81%
“…A similar distribution of gas-phase H 2 O in the midplane of a Herbig Ae disk is reported in Figure 1 of Woitke et al (2009b). Here we also note that Eistrup et al (2016) calculated the chemical evolution of a disk midplane under both molecular and atomic initial conditions as initial chemical abundances. They showed that in the latter atomic conditions, the abundance of H 2 O gas and ice around the H 2 O snowline (∼ 10 −6 ) is smaller than that for molecular initial abundances (∼ 10 −4 ).…”
Section: The Distributions Of H 2 O Gas and Icesupporting
confidence: 81%
“…The CO 2 ice content in the outer disk can be orders of magnitude higher. Both chemical models and measurements of comets show that the CO 2 content in ices can be more than 20% of the total ice content (Le Roy et al 2015;Eistrup et al 2016), with CO 2 ice even becoming more abundant than H 2 O ice in some models of outer disk chemistry (Drozdovskaya et al 2016). This translates into an abundance up to a few × 10 −5 .…”
Section: Tracing the Co 2 Icelinementioning
confidence: 99%
“…This result has been confirmed by physical-chemical modeling of the source, which was able to reproduce, among other lines, spatially resolved ALMA data and atomic carbon lines Schwarz et al 2016). This result is interpreted as chemical evolution, that is, carbon has been turned from CO into more complex species either in the gas or in the ice (Aikawa et al 1996;Bergin et al 2014;Drozdovskaya et al 2015;Eistrup et al 2016), or alternatively, as a grain growth effect, carbon has been locked up in large icy bodies that no longer participate in the gas-phase chemistry (Du et al 2015;Kama et al 2016), resulting in less bright CO lines. This hints at the possible existence of a class of disks where CO is not the main carbon reservoir.…”
Section: Introductionmentioning
confidence: 99%